Non-use phenomenon of CASE tools: Malaysian experience - Selamat, M.H.; Choong, C.Y.; Othman, A.T.; Rahim, MM (Elsevier, 1994)
Although computer-aided software engineering (CASE) technology has received widespread acceptance in the Western information systems community, many organizations in Malaysia are encountering difficulties in introducing CASE to automate their systems development tasks. It has been reported that CASE tools have failed to achieve success in a considerable number of Malaysian organizations. Therefore a study has been undertaken to examine the reasons that led to non-use of CASE tools. It is found that in Malaysia, the problems of non-use of CASE are human oriented, relating to CASE users, software managers and CASE vendors. Surprisingly, technical issues were found to have less impact in abandoning CASE products. The findings of this study are also compared with that of others conducted in the UK and USA. Some interesting observations are highlighted. Finally, it is advised that organizations should not move too quickly from the manual systems development approach to CASE environment. A strong commitment, adequate training and appreciation programs will, hopefully, minimize many of these problems.